Peacemaking and the challenge of violence in world religions - Omar, Irfan A.; Duffey, Michael K. (John Wiley, 2015)
Peacemaking and the Challenge of Violence in World Religions is a comprehensive exploration of the history, beliefs and practices around peace and violence in seven of the world's major religions. Written by expert practitioner-scholars, this textbook provides clear and systematic coverage of Buddhism, Christianity, Confucianism, Hinduism, Islam, Judaism, and Native American religion.